The Difference Effectiveness of Savlon and Nacl in Healing Post-operation Wound - Purnomo, Heru; Mu'awanah (International Journal of Psychosocial Rehabilitation, 2020)
Patients undergoing surgery will be at risk of infection. The incidence of surgical wound infections can be monitored early, and prevention is done immediately by providing wound care following procedures and with appropriate aseptic techniques, including using NaCl 0.9% or Savlon. The purpose of this study was to determine the differences in Savlon administration and 0.9% NaCl compress in the postoperative wound healing process in the Wijaya Kusuma Hospital, Dr. R Soetijono Blora. The research method used was a quasiexperimental design. The researcher provided postoperative wound care with Savlon fluid in the treatment group and NaCl 0.9% as a control group starting on day 3, day 5, and day 7 in postoperative patients. Samples in the study were all postoperative patients treated in the Wijaya Kusuma Hospital, Dr. R Soetijono Blora for three months who met the inclusion criteria. The sampling technique was 15 patients as a treatment group and 15 people as a control group. Data collection techniques used observation sheets and were analyzed descriptively and inferentially by employing the Mann-Whitney test. The process of healing postoperative wounds to respondents during treatment in days 3, 5, 7 using Savlon and NaCl 0.9% indicated wound healing was largely quite good. There is no significant difference in postoperative wound healing between the use of 0.9% NaCl and Savlon based on Asymp. Sig> 0.05. Postoperative wound care using Savlon and NaCl 0.9% generated effective results in the wound healing process.